2022
DOI: 10.3390/s22249962
|View full text |Cite
|
Sign up to set email alerts
|

Immersion Therapy with Head-Mounted Display for Rehabilitation of the Upper Limb after Stroke—Review

Abstract: Immersive virtual therapy technology is a new method that uses head-mounted displays for rehabilitation purposes. It offers a realistic experience that puts the user in a virtual reality. This new type of therapy is used in the rehabilitation of stroke patients. Many patients after this disease have complications related to the upper extremities that limit independence in their everyday life, which affects the functioning of society. Conventional neurological rehabilitation can be supplemented by the use of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…The high score in the Game Mechanics categories suggests that the participants found the exergame experience enjoyable, and perceived the graphics, sound, and overall technology to be of exceptionally high quality. Furthermore, the motion sickness index demonstrated that the exergame could be used without causing any adverse side effects [37] [47]. The satisfaction questionnaire revealed that participants were willing to embrace innovative approaches and viewed VR therapy as both useful and satisfying.…”
Section: Discussionmentioning
confidence: 99%
“…The high score in the Game Mechanics categories suggests that the participants found the exergame experience enjoyable, and perceived the graphics, sound, and overall technology to be of exceptionally high quality. Furthermore, the motion sickness index demonstrated that the exergame could be used without causing any adverse side effects [37] [47]. The satisfaction questionnaire revealed that participants were willing to embrace innovative approaches and viewed VR therapy as both useful and satisfying.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when using a VR headset, the user wears a special head-mounted display that fills the user's entire field of vision and gives them a very immersive 3D experience [44]. The user may also use specialized input devices, such as handheld controllers, to interact with the virtual environment.…”
Section: -2-vr Desktops and Vr Headsetsmentioning
confidence: 99%
“…Given the characteristics of modern HMDs, there are presently several ongoing studies to use them in the rehabilitation of neurological disorders such as multiple sclerosis [ 31 ] and stroke [ 32 ]. However, while the clinical outcomes of immersive VR-based rehabilitation interventions have been thoroughly investigated [ 32 , 33 , 34 ], their potential use as kinematic measurement devices has receive significant less attention. In particular, very few studies have analyzed the kinematic accuracy of HMDs compared to marker-based systems [ 35 , 36 , 37 , 38 ] and no study has investigated HMDs’ hand-tacking precision in post-stroke subjects.…”
Section: Introductionmentioning
confidence: 99%